The impact of pelvic floor electrical stimulation on vaginal microbiota and immunity - Zhang, Yakun; Yang, He; Zhang, Chi; Lin, Li; Yang, Wenlan; Xiong, Guangwu; Gao, Guolan (Frontiers in Cellular and Infection Microbiology, 2022)
Pelvic floor electrical stimulation (ES) is an effective treatment for pelvic floor dysfunction (PFD). However, the effects of ES on vaginal microbiota and local inflammatory are unknown. Therefore, we designed a longitudinal study to investigate the effect of ES on vaginal microbiota and cytokines. We recruited 170 participants at Peking University International Hospital Beijing, China from December 2021 to April 2022. They were divided into long protocol cohort (n=147) following up to 7 times therapies and short time cohort (n= 23) following up to 7h after 30min treatment. We acquired paired vaginal secretions from 134 individuals finally. The vaginal microbiota were detected by 16S rRNA sequencing and local cytokines concentrations were detected by CBA method. We found that the relative abundance of Lactobacillus spp. was significantly higher after ES (P＜0.001). In addition, L. crispatus (P=0.012) and L. gasseri (P=0.011) showed significant increases. The diversity of vaginal microbiota was modestly lower after ES. Furthermore, the significant downregulation of IFN-γ, IL-2, IL-4, IL-10, IL-17A and TNF-α in long protocol cohort was detected compared with baseline. However, a significant increase in IL-6 was found in short time cohort after treatment 7h. In conclusion, this study suggested that transvaginal electrical stimulation might assist in the dominance of Lactobacillus in vagina, reducing inflammation and even promoting recovery of vaginal microbiota to a certain extent.